Bathing study on four beaches of the Fernando de Noronha archipelago based on total coliform analysis (Research, Society and Development, 2021)
Environmental monitoring activities have been developed on the island of Fernando de Noronha, the Pernambuco Electrification Company is carrying out a series of studies on water, soil and air quality. For this, the Advanced Institute of Technology and Innovation promoted campaigns on the island to collect water quality data. With resources from the National Electric Energy Agency's Research and Development Program, six trips were scheduled during 2018 and 2019 for environmental quality studies. Four beaches were chosen for collections, two in the protected portion of the island and two in the area facing the oceanic zone. The samples from coliform studies were processed while on the island, through rapid tests with inoculation in 3M™ Petrifilm™ Plates and cultivation in a microbiological greenhouse. At the same time, water samples were collected for studies of basic physicochemical parameters. Regarding the analysis of coliforms, the beaches can be classified as Excellent bathing, as indicated in Resolution 20 of CONAMA. The highest value recorded reached above 5,000 NMP/100g-1 for Porto beach, in a period of high tourist season. Although the recorded values are, in general, in very good condition, studies of coliforms present in the sandy sediment would be important complementary for a more accurate diagnosis of the environmental quality of the studied beaches.